Everything you always wanted to know about systemic importance (but were afraid to ask) - Piergiorgio Alessandri; Sergio Masciantonio; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We develop a methodology to identify and rank systemically important financial institutions (SIFIs). Our approach is consistent with that followed by the Financial Stability Board (FSB) but, unlike the latter, it is free of judgment and it is based entirely on publicly available data, thus filling the gap between the official views of the regulator and those that market participants can form with their own information set. We apply the methodology to annual data on three samples of banks (global, EU and euro area) for the years 2007-2012. We examine the evolution of the SIFIs over time and document the shifs in the relative weights of the major geographic areas. We also discuss the implication of the 2013 update of the identification methodology proposed by the FSB.
Keywords: G21; G01; G18; 330; G-SIFIs; systemic risk; too-big-to-fail; financial crisis